Infection and autoimmunity in Sjogren's syndrome: A clinical study and comprehensive review (2014)
Sjögren's syndrome (SS) is an autoimmune disease characterized primarily by lymphocytic infiltration of the exocrine glands, and autoantibody production. Multiple environmental factors affecting an individual with a genetic susceptibility may trigger the development of SS. Herein, we aimed to evaluate links between the different pebbles in the mosaic of SS. Demographic, clinical data and blood samples were gathered from 82 consecutive patients with SS, and 139 healthy controls. Samples were analyzed for infectious serology and auto-antibodies as well as for relevant genetic mutations (TAP genes) and cytokines levels. An immune response (IgG) against Epstein-Barr virus (EBV) early antigen (EA) was positively associated with SS (OR 4; 95% CI: 1.82-8.83, p=0.001) while a protective effect of IgG anti-cytomegalovirus (CMV) was observed (OR 0.3; 95%CI: 0.16-0.74, p=0.009). Anti-Ro/SSA, anti-LA/SSB, anti-nuclear, anti-gliadin, anti-TTG-IgG and anti-RNP antibodies were statistically more prevalent among SS patients than controls. Notably, the presence of anti-Ro/SSA and anti La/SSB correlated with anti-EBVEA IgG (OR 3.1; 95%CI: 1.08-8.74) and (OR 3.9; 95%CI: 1.37-10.96) respectively. Autoantibodies, cytokines and several genetic markers correlated with clinical manifestation of SS. Our data suggest that infectious agents may play both a causative and protective role in the pathogenesis of SS. Moreover certain autoantibodies, cytokines and specific TAP alleles correlate with clinical manifestations of SS, and may enable better prediction and/or directed therapy once confirmed in future studies. © 2014 Elsevier Ltd.